An experimental test of a committee search model - Yoichi Hizen; Keisuke Kawata; Masaru Sasaki (Institute for the Study of Labor (IZA), 2012)
The objective of this paper is to design a laboratory experiment for an infinite-horizon sequential committee search model in order to test some of the implications obtained by the model in Albrecht, Anderson, and Vroman (2010) (AAV). We find that, compared with single-agent search, the search duration is longer for committee search under the unanimity rule, but is shorter for committee search in which at least one vote is required to stop searching. In addition, according to estimates from round-based search decisions, subjects are more likely to vote to stop searching in committee search than in single-agent search. This confirms that agents are less picky in committee search. Overall, the experimental outcomes are consistent with the implications suggested by the AAV model. However, despite the prediction from the AAV model, we could not obtain a significant outcome in relation to the size order of the probabilities of voting to stop searching in committee search for the various plurality voting rules.
Keywords: C91; D83; 330; experiments; committee search; plurality voting rules; Suchtheorie; Gruppenentscheidung; Theorie